Effect of Tea Polyphenols, α-Lipoic Acid and Their Joint Use on the Antioxidant and Lipid Metabolism Performance of Hybrid Grouper (♀Epinephelus fuscoguttatus × ♂E. lanceolatu) Fed with High-Lipid Diets - Xiangxiang Suo; Xiaobo Yan; Beiping Tan; Simiao Pan; Tao Li; Hao Liu; Weibin Huang; Shuang Zhang; Yuanzhi Yang; Xiaohui Dong (Aquaculture Nutrition)
This study investigated tea polyphenols (TP), α-lipoic acid (ALA) and their joint use on the antioxidant and lipid metabolic performance of hybrid grouper (♀Epinephelus fuscoguttatus × ♂E. lanceolatu) took food with high-fat diets. Six high-lipid diets with isonitrogen (50% of dry matter) and isolipid (17% of dry value) were designed, in which a total content of 1,000 mg/kg additives were added to each group except for the control group (FL). The additives addition ratios in each group were ALA (AL), TP (PL), ALA : TP = 1 : 1 (EL), ALA : TP = 1 : 2 (OL), ALA : TP = 2 : 1 (TL). Each diet was divided into three repeat groups with 30 tails (6.84 ± 0.01 g) in each group and fed for 8 weeks. The consequences were as follows: (1) the highest weight gain rate, specific growth rate, as well as the lowest feed conversion ratio and ingestion rate were discovered in the OL team, which were opposite to the TL group. (2) The body fat content and muscle fat content in the fish oil group were the lowest (P<0.05), while those of the TL group were the highest. (3) Serum catalase, glutathione peroxidase, total antioxidant capacity, and superoxide dismutase activities were the highest, and the content of reactive oxygen species was the lowest in the OL group. (4) The OL group has the highest hepatic lipase activity and the lowest very low-density lipoprotein content of the liver. In contrast, the TL group had the highest fatty acid synthetase (FAS) activity (P<0.05). (5) The oil-red aspects of liver tissue displayed lipid particles in other groups were reduced to different degrees compared with FL group, and the OL group showed the best lipid-lowering effect. (6) Compared with the FL group, the relative expressions of FAS, acetyl-CoA carboxylase (acc), and apolipoprotein b-100 (apoB100) genes in the liver were decreased. The relative expressions of lipoprotein lipase (lpl) and peroxisome proliferators-activated receptors-α (pparα) genes related to lipid catabolism were increased, among which the OL group had the most significant change (P<0.05). (7) According to the 7-day challenge test of Vibrio alginolyticus, the OL group had the highest survival rate. To sum up, both ALA and TP have positive effects on relieving the lipid metabolism disorder of hybrid grouper. If they are jointly used, adding ALA : TP in a ratio of 1 : 2 (OL) may have the best effect, and an addition ratio of 2 : 1 (TL) may inhibit the hybrid grouper growth and increase the feeding cost.